Economic evaluation of fungicides for leaf blight (Alternaria alternata) control in the transplanted crop of 'Shivalik' menthol mint (Mentha arvensis) - KALRA, A; SINGH, H B; PATRA, N K; KUMAR, SUSHIL (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during rainy (kharif) season of 1997,1998 and 1999 to evaluate the different fungicides for control of leaf blight of menthol mint (Mentha arvensis L.) caused by Alternaria alternata (Fr.) Keissler and to determineÂ  most economical optimal application schedule. Chlorothalonil provided maximum disease control, though the other fungicides mancozeb, thiophanate-methyl and copper oxychloride were also effective. The chlorothalonil- sprayed plots gave 45% greater yield of essential oil compared with the unsprayed plots. Three applications of chlorothalonil at 15-day intervals provided economically acceptable disease control with maximum increase (40%) in essential oil yields and total net returns (Rs 7 700).